Red flags to screen for malignancy and fracture in patients with low back pain: systematic review - Downie, Aron; Williams, Christopher M.; Henschke, Nicholas; Hancock, Mark J.; Ostelo, Raymond W. J. G.; Vet, Henrica C. W. de; Macaskill, Petra; Irwig, Les; Tulder, Maurits W. van; Koes, Bart W.; Maher, Christopher G. (The BMJ, 2013)
Objective To review the evidence on diagnostic accuracy of red flag signs and symptoms to screen for fracture or malignancy in patients presenting with low back pain to primary, secondary, or tertiary care. - Design Systematic review. - Data sources Medline, OldMedline, Embase, and CINAHL from earliest available up to 1 October 2013. - Inclusion criteria Primary diagnostic studies comparing red flags for fracture or malignancy to an acceptable reference standard, published in any language. - Review methods Assessment of study quality and extraction of data was conducted by three independent assessors. Diagnostic accuracy statistics and post-test probabilities were generated for each red flag. - Results We included 14 studies (eight from primary care, two from secondary care, four from tertiary care) evaluating 53 red flags; only five studies evaluated combinations of red flags. Pooling of data was not possible because of index test heterogeneity. Many red flags in current guidelines provide virtually no change in probability of fracture or malignancy or have untested diagnostic accuracy. The red flags with the highest post-test probability for detection of fracture were older age (9%, 95% confidence interval 3% to 25%), prolonged use of corticosteroid drugs (33%, 10% to 67%), severe trauma (11%, 8% to 16%), and presence of a contusion or abrasion (62%, 49% to 74%). Probability of spinal fracture was higher when multiple red flags were present (90%, 34% to 99%). The red flag with the highest post-test probability for detection of spinal malignancy was history of malignancy (33%, 22% to 46%). - Conclusions While several red flags are endorsed in guidelines to screen for fracture or malignancy, only a small subset of these have evidence that they are indeed informative. These findings suggest a need for revision of many current guidelines.